2010
DOI: 10.2527/jas.2009-1993
|View full text |Cite
|
Sign up to set email alerts
|

Fermented soybean meal as a vegetable protein source for nursery pigs: I. Effects on growth performance of nursery pigs

Abstract: Four experiments were conducted using 671 nursery pigs to evaluate fermented soybean meal (FSBM) as a new vegetable protein source for nursery pigs. In Exp. 1, a total of 192 pigs weaned at 19.2 +/- 0.3 d of age were fed 3 diets (8 pens per treatment) for 2 wk: a control diet (without FSBM) and 2 diets with 3 and 6% FSBM replacing soybean meal, followed by a common diet for the next 2 wk. In Exp. 2, a total of 160 pigs weaned at 21.6 +/- 0.2 d of age were fed 4 diets (5 pens per treatment) for 2 wk: a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 42 publications
2
90
0
Order By: Relevance
“…Cho et al (2007) reported that piglets fed fermented soya beans showed increased feed efficiency. The study of Kim et al (2010) also documented that during nursery pigs at 3 to 7 wk of age, a significant increase of ADG and ADFI were observed in treatments fed fermented soybean meal. Furthermore it can serve as an alternative protein source for possibly replacing the use of dried skim milk and plasma protein.…”
Section: Discussionmentioning
confidence: 93%
“…Cho et al (2007) reported that piglets fed fermented soya beans showed increased feed efficiency. The study of Kim et al (2010) also documented that during nursery pigs at 3 to 7 wk of age, a significant increase of ADG and ADFI were observed in treatments fed fermented soybean meal. Furthermore it can serve as an alternative protein source for possibly replacing the use of dried skim milk and plasma protein.…”
Section: Discussionmentioning
confidence: 93%
“…Concentrations of digestible energy (DE) and metabolizable energy (ME) may also be affected by fermentation (Rojas and Stein, 2013). Consequently, FSBM may be used to replace other high quality protein sources without adversely affecting the performance of nursery pigs (Kim et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Feng et al (2007) showed that FSBM with a low concentration of glycinin and β-conglycinin could improve feed intake and average daily weight in piglets. However, a diet containing only 9% FSBM with a 40% reduction in glycinin and β-conglycinin did not improve the growth performance of weaned pigs (Kim, Van Heugten, Ji, Lee, & Mateo, 2010). Thus, highly efficient allergen degradation strains are essential in the creation of FSBM, in order to improve animal growth performance.…”
Section: Introductionmentioning
confidence: 99%